HUBUNGAN ANTARA BODY CONDITION SCORE (BCS) DENGAN PRODUKSI SUSU SAPI PERAH FRIESIAN HOLSTEIN (FH) - Netika, Melsa; Darsono, Roesno; Utomo, Budi; Mustofa, Imam; Ismudiono, Ismudiono; Suprayogi, Tri Wahyu (Universitas Airlangga, 2019)
The aim of this research was to observe the Body Condition Score (BCS) and milk production of Friesian Holstein (FH) dairy cattles. 144 of dairy cattles divided into 3 groups based on BCS 1-9 scale. The results showed that Y = 6.62 + 5.54X - 5.78X2. Coefficient of determination (R2) of 20.6 this mean any increase in milk production by 20.6% is affected by BCS. It can be concluded that there is a correlation between Body Condition Score (BCS) and milk production. The higher BCS (BCS 7-8) the lower milk production, while in ideal BCS production (5-6) the production of milk is optimize.